Breeding Season Space Use and Habitat Selection of Adult Female Scaled and Gambel's Quail in West Texas - Richard A. Temple; Louis Harveson; Ryan S. Luna (National Quail Symposium Proceedings, 2017)
We used radiotelemetry to investigate breeding-season (1 Apr–1 Sep, 2012 and 2013) home ranges and habitat selection of adult female scaled (Callipepla squamata) and Gambel’s quail (C. gambelii) in the eastern Chihuahuan Desert, Texas. Mean breeding-season home range (95% fixed kernel) for scaled quail was 145.02 ± 23.56 ha (range = 22.03–538.24 ha) and 156.32 ± 13.04 ha (range = 66.15– 270.74 ha) for Gambel’s quail. Mean core-use area (50% fixed kernel) for scaled quail was 31.38 ± 4.80 ha (range = 4.03–111.36 ha) and 32.87 ± 2.61 ha (range = 12.19–52.36 ha) for Gambel’s quail. We found evidence of home-range overlap in neighboring females in both species. Excessive drought can suppress nesting activity. However, encourage reproductive activity in both species may be encouraged by managing riparian areas to provide adequate forage and microclimatic conditions.
Keywords: breeding season; callipepla gambelii; callipepla squamata; Gambel& #x27; s quail; habitat use; scaled quail